151k views
0 votes
The first three steps in determining the solution set of the system of equations algebraically are shown.

y = x2 − x − 3
y = −3x + 5



What are the solutions of this system of equations?

User Khai Vu
by
6.0k points

1 Answer

4 votes

Answer:

(- 4, 17 ) and (2, - 1 )

Explanation:

Given the 2 equations

y = x² - x - 3 → (1)

y = - 3x + 5 → (2)

Substitute y = x² - x - 3 into (2)

x² - x - 3 = - 3x + 5 ( subtract - 3x + 5 from both sides )

x² + 2x - 8 = 0 ← in standard form

(x + 4)(x - 2) = 0 ← in factored form

Equate each factor to zero and solve for x

x + 4 = 0 ⇒ x = - 4

x - 2 = 0 ⇒ x = 2

Substitute these values into (2) for corresponding values of y

x = - 4 : y = - 3(- 4) + 5 = 12 + 5 = 17 ⇒ (- 4, 17 )

x = 2 : y = - 3(2) + 5 = (- 6 + 5 = - 1 ⇒ (2, - 1 )

User Probablybest
by
5.6k points